MARRIAGE READINESS OF ADOLESCENTS AGED 20-24 IN INDONESIA - Murniati, Chairunnisa; Pujihasvuty, Resti; Nasution, Sri Lilestina; Oktriyanto, Oktriyanto; Amrullah, Hilma (Jurnal Biometrika dan Kependudukan, 2024)
Readiness for marriage in adolescents aged 20-24 years shows readiness to change roles and new responsibilities as husband and wife, manage the family, and raise children. This study aims to obtain information and an overview of the readiness for marriage in adolescents in Indonesia aged 20-24 from 10 aspects of readiness. The research used a quantitative approach, targeting unmarried youth aged 20-24 in Indonesia. The instrument used is a structured questionnaire distributed via a Google Form ® link. Data analysis used the scoring method to measure the index of youth readiness in family life. This study classifies adolescents' readiness scores in family life into two categories: ready and not ready, with a cut-off of 80. If the readiness value is ≥80, it is categorized as ready, whereas if the readiness index value is <80, it is classified as not ready. The result shows the index of family readiness for adolescents aged 20-24 years in Indonesia is 79.21. It means that adolescents aged 20-24 years in Indonesia are still categorized as not ready to live with a family. The ten dimensions of readiness classified "as not yet ready" are financial, age and planning aspects of marriage, emotional, physical, intellectual, and social aspects. In contrast, readiness aspects categorized as "ready" are life skills, mental, interpersonal, and moral aspects.